Attitudes toward Management of Sickle Cell Disease and Its Complications: A National Survey of Academic Family Physicians - Arch G. Mainous; Rebecca J. Tanner; Christopher A. Harle; Richard Baker; Navkiran K. Shokar; Mary M. Hulihan (Anemia)
Objective. Sickle cell disease (SCD) is a disease that requires a significant degree of medical intervention, and family physicians are one potential provider of care for patients who do not have access to specialists. The extent to which family physicians are comfortable with the treatment of and concerned about potential complications of SCD among their patients is unclear. Our purpose was to examine family physician’s attitudes toward SCD management. Methods. Data was collected as part of the Council of Academic Family Medicine Educational Research Alliance (CERA) survey in the United States and Canada that targeted family physicians who were members of CERA-affiliated organizations. We examined attitudes regarding management of SCD. Results. Overall, 20.4% of respondents felt comfortable with treatment of SCD. There were significant differences in comfort level for treatment of SCD patients depending on whether or not physicians had patients who had SCD, as well as physicians who had more than 10% African American patients. Physicians also felt that clinical decision support (CDS) tools would be useful for treatment (69.4%) and avoiding complications (72.6%) in managing SCD patients. Conclusions. Family physicians are generally uncomfortable with managing SCD patients and recognize the utility of CDS tools in managing patients.